OP20 Shame: experiences of food and poverty among white british and pakistani low-income women. (2nd September 2017) - Power, MS; Small, N; Pickett, KE
Abstract : Background: Food bank use has increased sharply in the UK since 2010, however, qualitative research with food aid providers has found very low use of food banks by members of Bradford's Pakistani community, a large minority community in Bradford. Despite this, quantitative research has shown a substantial prevalence of food insecurity among Pakistani households (10%), albeit a lower prevalence than in White British (WB) households (18%). The study aims to understand how low-income women understand and experience food insecurity, and how this differs between WB and Pakistani women; and to explore access to and experiences of food aid among WB and Pakistani low-income women. Methods: In light of potential recruitment difficulties and language and capacity restrictions, focus groups were used. With the assistance of the Better Start Bradford Innovation Hub, we identified existing group activities in Bradford where it would be appropriate to hold focus groups. Members of these groups were invited to participate in the study. Four semi-structured focus groups (n=16) were conducted in three low-income wards in Bradford. A three-stage analysis process was used and the data was analysed thematically. Results: The sample included eight Pakistani women and eight WB women living in three deprived wards in Bradford. Seven Pakistani women were married to men in employment. Only one Pakistani woman was in employment. Six WB women were married or cohabiting; one was employed; four had partners who were employed and three were solely reliant on social security. Only one Pakistani women reported struggling to afford food, compared with five WB women. However, only three of the latter had used food aid; no Pakistani women had used food aid. All women described a sense of shame around not being to provide enough food for family members, particularly children. This was felt most acutely among Pakistani women. It was explained that food insecurity was experienced but concealed among Bradford's Pakistani community; support with food was sought not from food aid but from immediate family members and, occasionally, the wider Pakistani community. Conclusion: This is small scale study of low income women in one city, however it does suggest that Pakistani and WB women in Bradford experience food insecurity differently, with the latter much more likely to use food banks. Shame around food insecurity may not only deter low-income women from accessing food aid but cause food insecurity to be concealed entirely, this is most pronounced in the Pakistani community.